2007
DOI: 10.1136/ip.2007.015396
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral assessment of child-directed canine aggression

Abstract: Most children were bitten by dogs with no history of biting children. There is a high rate of behavioral abnormalities (aggression and anxiety) in this canine population. Common calming measures (neutering, training) were not routinely effective deterrents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 16 publications
4
87
0
4
Order By: Relevance
“…Our survey further showed that one quarter of the children were bitten when playing with dogs, others when stroking them, when disturbing them during rest, sleep or eating. Other situations were similar to those described by Reisner et al (2007). The injuries were contracted mostly during indoor interactions in which small size dogs prevailed.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Our survey further showed that one quarter of the children were bitten when playing with dogs, others when stroking them, when disturbing them during rest, sleep or eating. Other situations were similar to those described by Reisner et al (2007). The injuries were contracted mostly during indoor interactions in which small size dogs prevailed.…”
Section: Discussionsupporting
confidence: 58%
“…Akhtar et al 2006;Wake et al 2006;Kaye et al 2009). In the study of Reisner et al (2007), 6-year old children were bitten in association with resource guarding whereas older children were most commonly bitten in association with guarding territory. Our findings corroborate this description.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las razas de mayor agresividad, y por lo tanto con más riesgo de mordeduras, de acuerdo a varios estudios, son las siguientes, incluidas sus cruzas: Pastor alemán, Rottweiler, Pit bull, ChowChow y Akitas [55][56][57][58][59][60][61] . Sin embargo, se debe tener presente que en cada raza hay individuos de mayor docilidad y otros más agresivos y dominantes, por lo que es muy importante la evaluación conductual de cada animal.…”
Section: Elección De La Mascota Caninaunclassified
“…Sin embargo, se debe tener presente que en cada raza hay individuos de mayor docilidad y otros más agresivos y dominantes, por lo que es muy importante la evaluación conductual de cada animal. Además, se deben evitar ciertas conductas de las personas que pueden desencadenar agresividad en el perro 58 , tales como invadir su comida cuando está alimentándose, establecer contacto físico con animales desconocidos o conocidos pero con antecedentes previos de mordeduras y la presencia de niños pequeños en compañía del animal sin la supervisión de un adulto 55,59 .…”
Section: Elección De La Mascota Caninaunclassified